SHEEP PRODUCTION DEVELOPMENT STRATEGY IN EAST BATURAJA SUB DISTRICT OKU REGENCY - Febrika Indra,; Fifian, Fifian Permata Sari; Rini Efrianti, (International Journal of Social Science, 2022)
This study aims to analyze the strategy of increasing sheep production in East Baturaja Sub District, Ogan Komering Ulu Regency, South Sumatra Province. This research was conducted in Baturaja Timur District, OKU Regency at February 2022, the research method used was a survey method with a saturated random sampling method of 15 samples. The analytical tool used is a SWOT analysis, analyzing internal and external factors in the development of a sheep farming business and finding strategies that can be applied in Baturaja Timur District in particular and in OKU District in general. The results of the study indicate that strategies that can be applied to increase the production of sheep farming in Baturaja Timur District, OKU Regency include: utilizing abundant forage feed to be used as animal feed, good livestock adaptation to the environment, then easier access to transportation and processing of livestock waste into organic fertilizer. In addition, it is necessary to increase the utilization of the potential of pasture land for livestock.